Physician Satisfaction with Anti-Inflammatory Topical Medications for the Treatment of Dry Eye Disease - White DE (Dove Medical Press, 2020)
Darrell E White,1 Yang Zhao,2 Hemalatha Jayapalan,3 Pattabhi Machiraju,3 Ramu Periyasamy,3 Abayomi Ogundele2 1SkyVision Centers, Westlake, OH, USA; 2Medical Affairs, Sun Pharmaceutical Industries, Princeton, NJ, USA; 3Medical Services, Indegene, Inc, Bangalore, IndiaCorrespondence: Abayomi OgundeleMedical Affairs, Sun Pharmaceutical Industries, Inc, 2 Independence Way, Princeton, NJ 08540, USAEmail abayomi.ogundele@sunpharma.comPurpose: Dry eye disease (DED) is one of the most common ophthalmic disorders. Pathogenesis of the disease includes inflammation of the ocular surface and lacrimal gland. Two anti-inflammatory prescription treatments are currently available: cyclosporine ophthalmic emulsion 0.05% (CYC) and lifitegrast 5% ophthalmic solution (LIF). The objective of this survey-based study was to assess physician satisfaction with CYC and LIF for the treatment of DED.Methods: Physicians currently treating DED patients with CYC or LIF were asked to rate the experiences of their patients currently or formerly using CYC and LIF, and their own perspectives on the two treatments.Results: Twenty-one physicians participated in the survey, providing responses on behalf of 210 patients. Overall, physicians reported low levels of satisfaction with onset of action of CYC and LIF, and fewer than half considered either drug to be effective in managing symptoms or improving patient quality of life (QoL). Burning sensation and dysgeusia were the most frequently reported side effects. Onset of action and effectiveness after onset were the main switching drivers. Although two-thirds of physicians were satisfied with the overall effectiveness of CYC and LIF, all physicians agreed that more DED treatment options are needed, with > 50% strongly agreeing.Conclusion: Physicians perceived a gap in DED management with currently available topical anti-inflammatory agents. Although satisfaction with CYC and LIF was high, few physicians considered these medications to be effective in managing symptoms or improving QoL.Keywords: physician satisfaction, dry eye disease, cyclosporine, lifitegrast, ocular surface